Clinical and Ultrasonographic Correlates of Knee Pain in Patients with Type 2 Diabetic Mellitus in a Nigerian Tertiary Hospital - Aderibigbe, A S; Ayoola, O O; Kolawole, B A; Esan, O (West African journal of medicine, 2025)
To ascertain the prevalence of knee pain in type 2 diabetic mellitus (T2DM) patients and to compare associated structural ultrasonographic arthritic changes with non-diabetic controls. Associations between T2DM knee pain, clinical variables and ultrasonographic arthritic changes were also investigated. Using a high frequency linear ultrasound probe (7.5-12MHz), both knees of 78 consecutive T2DM patients and 30 age and sex matched non-diabetic controls without knee pain were scanned. Seventy-eight T2DM patients and 30 controls with mean ages of 63.0±10.4years (M:F = 1:1.9) and 2.3±10.5years (M:F = 1:0.9) respectively were studied. Forty (51.8%) T2DM patient presented with unilateral or bilateral knee pain while clinical pes anserinus tendinitis bursitis syndrome (PATBS) was diagnosed exclusively in 8 female T2DM patients, constituting 10.0% of the total T2DM group. At least 1 positive ultrasonographic arthritic change was found in 98.5% T2DM knees with pain, 86.8% T2DM knee without pain, and 69.2 % control knees (p< 0.05). Independent predictors of knee joint pain are age >60 years (OR=3.5), obesity (OR=2.9), and medial meniscal protrusion (OR=8.7). Ultrasonographic arthritic changes are highly prevalent in T2DM patients with and without knee pain. Independent predictors of knee joint pains are age > 60 years, obesity, and medial meniscal protrusion.